Dampak Influencer Marketing terhadap Purchase Decision dengan Brand Trust dan Brand Image sebagai Intervening: (Studi pada Pengguna Brand PIXY pada Gen Z di Kota Cilegon) - Adytia Rahadatul Aisy; Asep Supriadi; Hayati Nupus (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to determine the effect of influencer marketing on purchase decisions with brand trust and brand image as intervening variables, focusing on users of PIXY compact powder cosmetics among Generation Z in Cilegon City. The research method employed was quantitative, utilizing data collected through questionnaires and a literature review. The study population consisted of 160 respondents who met the criteria of being part of Generation Z and users of PIXY compact powder cosmetics. The sampling technique employed was non-probability sampling, specifically accidental sampling. The analysis method employed was Structural Equation Modeling (SEM), utilizing the statistical tool SmartPLS 4 Professional for analysis.The results of this study: influencer marketing has a negative but insignificant effect on purchase decision, influencer marketing has a positive and significant effect on brand trust, influencer marketing has a positive and significant effect on brand image, brand trust has a positive and significant effect on purchase decision, brand image has a positive and significant effect on purchase decision, brand trust has a positive and significant mediating effect on influencer marketing toward purchase decision, brand image has a positive and significant mediating effect on influencer marketing toward purchase decision.